Analisis Pengaruh Current Ratio dan Net Profit Margin terhadap Harga Saham Pada Perusahaan Jasa Sub Sektor Perdagangan Besar (Grosir) Dimasa Pandemi Covid-19 Periode 2020-2021 (Studi Kasus pada Bursa Efek Indonesia) - Aprilia Wulan; Budiono Budiono; Dwi Puji Rahayu Rahayu; Indrian Supheni; Wina Aprilia Purnamasari (Yayasan Literasi Ilmiah Indonesia, 2023)
This study aims to determine the effect of the current ratio and net profit margin on stock pricescarried out by large (wholesale) sub-sector trading service companies listed on the Indonesia StockExchange. The population of this study is a large trading sub-sector (wholesale) service companylisted on the IDX in 2020-2021. The sample was determined based on the purposive sampling method,as many as 110 companies.The method used in this study is a quantitative method. This method is used to predict the influencebetween one variable and another, in this study, the variables X1 (Current Ratio) and X2 (Net ProfitMargin) are the dependent variable (free) and the Y variable (Stock Price) is the independent variable(bound). ), the instrument used is secondary data and simple regression analysis is used to analyzethe data.The results in this study are the variable Current Ratio (CR) has a negative and significant effect onstock prices, Net Profit Margin (NPM) has a positive and significant effect on stock prices. CurrentRatio (CR) and Net Profit Margin (NPM) together have a significant effect on stock prices. The studyshows that the current ratio has a negative and significant effect on stock prices, net profit marginshave a positive effect on stock prices.